The Effects of Task Focus and Involvement Load on Idioms Recognition - Maryam Mousavi; Abbas Ali Zarei; Saeideh Ahangari (Journal of Modern Research in English Language Studies)
This study investigated the effects of form-focused and meaning-focused tasks with different involvement load indices on EFL learners' recognition of L2 idioms. To this end, a sample of 180 EFL learners (both male and female) in two language institutes was selected and randomly assigned into six groups. Form-focused tasks with involvement load 2 (Multiple-choice), 3 (Sentence-completion), 4 (Sentence-making) were used for three experimental groups, while meaning-focused tasks with involvement load 2 (Summary-writing), 3 (Writing with glossary), and 4 (Writing without glossary) were utilized for the other three groups. After the treatment, a 30-item test in multiple-choice format was administered to assess the participants' recognition of idioms. One two-way ANOVA and a series of independent-samples t-tests were run to process the collected data. The results indicated that the tasks with higher levels of involvement load were more effective on recognition of idioms. The results also showed that form-focused tasks were more efficient than meaning-focused tasks. Moreover, at involvement load of two, meaning-focused tasks were more beneficial than form-focused tasks, while form-focused tasks were more effective at higher involvement loads of three and four. The results of this study can have theoretical and pedagogical implications for language teachers, curriculum designers, and researchers.